Leisure Island: An Investigation of Suburban Landscapes and Domestic Spaces in South Africa - Lilford, Kirsten Lee (Michaelis School of Fine Art, 2024)
Media and communications analyst, Roger Silverstone (1997) brings our attention to the negative elements of the suburban landscape, a space more often associated with the comfortable life – one filled with luscious garden lawns, large crystal blue swimming pools, double garages and domestic workers' quarters. That this domestic space has ‘protected' itself from the stress of the city through the use of high walls, electric fences and wrought iron gates, is an irony worth commenting on. As Silverstone notes, this constructed paradise is not without its complications.